Advances in Microfluidics Technology for Diagnostics and Detection - Kinahan, David; Mager, Dario; Vereshchagina, Elizaveta; Miyazaki, Celina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Microfluidics and lab-on-a-chip have, in recent years, come to the forefront in diagnostics and detection. At point-of-care, in the emergency room, and at the hospital bed or GP clinic, lab-on-a-chip offers the potential to rapidly detect time-critical and life-threatening diseases such as sepsis and bacterial meningitis. Furthermore, portable and user-friendly diagnostic platforms can enable disease diagnostics and detection in resource-poor settings where centralised laboratory facilities may not be available. At point-of-use, microfluidics and lab-on-chip can be applied in the field to rapidly identify plant pathogens, thus reducing the need for damaging broad spectrum pesticides while also reducing food losses. Microfluidics can also be applied to the continuous monitoring of water quality and can support policy-makers and protection agencies in protecting the environment. Perhaps most excitingly, microfluidics also offers the potential to enable entirely new diagnostic tests that cannot be implemented using conventional laboratory tools. Examples of microfluidics at the frontier of new medical diagnostic tests include early detection of cancers through circulating tumour cells (CTCs) and highly sensitive genetic tests using droplet-based digital PCR.This Special Issue on "Advances in Microfluidics Technology for Diagnostics and Detection" aims to gather outstanding research and to carry out comprehensive coverage of all aspects related to microfluidics in diagnostics and detection.